2013
DOI: 10.1177/0954410013498056
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermodynamics of a hypersonic vehicle with a forward-facing parabolic cavity at nose

Abstract: Numerical experiments are carried out using commercially available Navier–Stokes solver to investigate the effect of forward-facing parabolic cavity on the heat fluxes over a spherical nosed blunt body. A wide range of parabolic cavities with depths varying between 2 and 10 mm placed at the nose of sphere-cylinder with base diameter 40 mm and overall length 70 mm have been investigated. The ratio of the cavity radius at intersection with y-axis to depth of cavity ( r/d) of these cavities varies from 1.5 to 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, air downstream of the fore shock creates an annular vortex structure around the inner lip of the cavity. This vortex acts to isolate the new stagnation zone (inside the cavity) from the high-enthalpy flow upstream [225]. For both deep and shallow cavities, a local excessive heat flux is attained at the lip of the cavity that may exceed that at the stagnation point of the forebody without the cavity.…”
Section: Combined Jet-cavity Devicementioning
confidence: 99%
“…On the other hand, air downstream of the fore shock creates an annular vortex structure around the inner lip of the cavity. This vortex acts to isolate the new stagnation zone (inside the cavity) from the high-enthalpy flow upstream [225]. For both deep and shallow cavities, a local excessive heat flux is attained at the lip of the cavity that may exceed that at the stagnation point of the forebody without the cavity.…”
Section: Combined Jet-cavity Devicementioning
confidence: 99%
“…The influence of a forward-facing cavity on heat transfer and aerodynamic coefficients has been investigated by Saravanan et al (2009), and the deepest cavity shows better heat flux reduction (Silton and Goldstein, 2005;Lu and Liu, 2012b;Yadav and Guven, 2014). The mechanism of heat reduction induced by a forward-facing cavity has been by many researchers (Huebner and Utreja, 1993;Engblom et al, 1997), and the cooling effect is produced by the oscillation of the bow shock wave (Ladoon et al, 1998).…”
Section: Combination Of Counterflowing Jet and Forward-facing Cavitymentioning
confidence: 99%
“…Hypersonic vehicles such as hypervelocity projectiles, re-entry vehicles and hypersonic aircraft are designed to withstand severe heat loads. A proposed heat transfer reduction mechanism is to locate a forward-facing cavity at the nose tip [1][2][3][4][5]. It was reported that the heat flux at the cavity base could be as little as 2 to 10 times less than the stagnation point of a conventional convex hemispherical tip [6].…”
Section: Introductionmentioning
confidence: 99%